Key Determinants of International Retail Success: A Case of IKEA Retail - Singh, Padmalini; Rao, K.S. Srinivasa; Xuan, Liang; Kee, Daisy Mui Hung; Min, Fong Jia; Xuan, Tan Yi; Ing, Teoh Siew; Malhotra, Kunal; Pandey, Rudresh (AIBPM Publisher, 2021)
IKEA is an internationally well-known largest furniture retailer. The purpose of this study is to study key determinants of IKEA's success. To reach the purpose of this research, we focused on the international strategy IKEA used to approach their customers and IKEA’s SWOT analysis. Besides, we also focus on how IKEA store layout influences consumer behavior. The primary data collection method was interviews conducted with IKEA customers by Google forms. This study found that IKEA’s unique management planning and marketing strategy attract customers to revisit the retail store.